Synthesis, magnetic properties, and phosphoesterase activity of dinuclear cobalt(II) complexes - Daumann, Lena J.; Comba, Peter; Larrabee, James A.; Schenk, Gerhard; Stranger, Robert; Cavigliasso, German; Gahan, Lawrence R. (Inorganic chemistry, 2013)
A series of dinuclear cobalt(II) complexes has been prepared and characterized to generate functional and spectroscopic models for cobalt(II) substituted phosphoesterase enzymes such as the potential bioremediator GpdQ. Reaction of ligands based on 2,2′-(((2-hydroxy-5-methyl-1,3-phenylene)bis(methylene))bis((pyridin-2-ylmethyl)azanediyl)))diethanol (L1) and 2,6-bis(((2-methoxyethyl)(pyridin-2-ylmethyl)amino)methyl)-4-methylphenol (L2) with cobalt(II) salts afforded [Co2(CO2EtH2L1)(CH3COO)2](PF6), [Co2(CO2EtL2)(CH3COO)2](PF6), [Co2(CH3L2)(CH3COO)2](PF6), [Co2(BrL2)(CH3COO)2](PF6), and [Co2(NO2L2)(CH3COO)2](PF6). Complexes of the L2 ligands contain a coordinated methyl-ether, whereas the L1 ligand contains a coordinated alcohol. The complexes were characterized using mass spectrometry, microanalysis, X-ray crystallography, UV-vis-NIR diffuse reflectance spectroscopy, IR absorption spectroscopy, solid state magnetic susceptibility measurements, and variable-temperature variable-field magnetic circular dichroism (VTVH MCD) spectroscopy. Susceptibility studies show that [Co2(CO2EtH2L1)(CH3COO)2](PF6), [Co2(CO2EtL2)(CH3COO)2](PF6), and [Co2(CH3L2)(CH3COO)2](PF6) are weakly antiferromagnetically coupled, whereas [Co2(BrL2)(CH3COO)2](PF6) and [Co2(NO2L2)(CH3COO)2](PF6) are weakly ferromagnetically coupled. The susceptibility results are confirmed by the VTVH MCD studies. Density functional theory calculations revealed that magnetic exchange coupling occurs mainly through the phenolic oxygen bridge. Implications of geometry and ligand design on the magnetic exchange coupling will be discussed. Functional studies of the complexes with the substrate bis(2,4-dinitrophenyl) phosphate showed them to be active towards hydrolysis of phosphoester substrates.
Gesehen am 10.12.2020